2019
DOI: 10.1186/s12943-019-1108-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: N6-methyladenosine induced miR-143-3p promotes the brain metastasis of lung cancer via regulation of VASH1

Abstract: BackgroundBrain metastasis (BM) is one of the principal causes of mortality for lung cancer patients. While the molecular events that govern BM of lung cancer remain frustrating cloudy.MethodsThe miRNA expression profiles are checked in the paired human BM and primary lung cancer tissues. The effect of miR-143-3p on BM of lung cancer cells and its related mechanisms are investigated.ResultsmiR-143-3p is upregulated in the paired BM tissues as compared with that in primary cancer tissues. It can increase the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(167 citation statements)
references
References 56 publications
(69 reference statements)
1
162
0
4
Order By: Relevance
“…21 Another m 6 A methyladenosine METTL3 (m 6 A writer) induced miR-143-3p has been reported to promote the brain metastasis of lung cancer via regulation of VASH1. 22 In addition, Liu et al demonstrated that m 6 A demethylase FTO (m 6 A eraser) promotes cell proliferation and invasion in lung squamous cell carcinoma by regulating MZF1 expression. 23 However, m 6 A binding proteins (m 6 A readers) remain unexplored in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…21 Another m 6 A methyladenosine METTL3 (m 6 A writer) induced miR-143-3p has been reported to promote the brain metastasis of lung cancer via regulation of VASH1. 22 In addition, Liu et al demonstrated that m 6 A demethylase FTO (m 6 A eraser) promotes cell proliferation and invasion in lung squamous cell carcinoma by regulating MZF1 expression. 23 However, m 6 A binding proteins (m 6 A readers) remain unexplored in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 facilitates the maturation of pri-miR-1246 to enhance the metastasis of colorectal cancer (CRC) [49]. METTL3 also accelerates the maturation of miR-143-3p, leading to the formation of METTL3/miR-143-3p/vasohibin-1 axis to favor the metastasis of lung cancers [50].…”
Section: A Modification Of Mirnas In Cancermentioning
confidence: 99%
“…MiR-143-3p was identified as the key specific mediator of KIAA1429 expression in osteosarcoma cells [36]. In addition, it is also involved in the regulation of cell proliferation in cervical cancer, esophageal cancer, breast cancer, lung cancer and other neoplasms [37][38][39][40]. MiR19b-3p has also been implicated in the pathogenesis of several cancers in humans [41,42].…”
Section: Discussionmentioning
confidence: 99%